Установлення характеру спільного антиоксидантного впливу токоферолів і флавоноїдів на процес окиснення олій - Аксьонова, Олена Федорівна; Демидова, Анастасія Олександрівна; Кіндрашина, Аліна Сергіївна; Березка, Тетяна Олександрівна (Харківський державний університет харчування та торгівлі, 2016)
Досліджено сумарний інгібуючий вплив токоферолів і флавоноїдів на процес окиснення олій. Доведено синергетичний ефект між токоферолами та флавоноїдами. Установлено, що екстрактивні речовини, одержані з пагонів чорниці, мають антиоксидантні властивості.

Plant flavonoids are not only physiologically important substances and antioxidants, which have been intensively studied in decades. For oil industry it is interesting to establish cooperation between flavonoids and the most common natural antioxidant oils – tocopherols. Tocopherols and flavonoids are antioxidants of type 1, that their inhibitory effect not associated with open circuit, and the destruction of molecules hydroperoxides. To improve the efficiency of tocopherol as an antioxidant, it should be used in mixtures with other inhibitors of oxidation. One of the areas of search oxidation inhibitors is highly efficient search of synergistic mixtures. Synergist provide significant increase antioxidant effects, so they can be used in smaller quantities. Studies have proven the existence of synergies between the studied substances. Antioxidant Research conducted on the impact of inhibitors of Volumetric installation by determining the oxidation kinetics of oils, such as setting the length of the induction period. The study was conducted in conditions of initiated oxidation, is the sample oil added a certain amount of nitrile izo-oleic acid. Constant speed initiation achieved by adding the same number of nitrile izo-oleic acid. As plant extracts contain flavonoids, oak bark, nettle, marigold, mint, blueberry shoots were selected. Inhibitory effect of antioxidants mounted relative to the sample of refined sunflower oil. Oils always contain a certain amount of tocopherols, since the last addition does not add oil and natural investigated antioxidant effect of tocopherols number. The values of synergies between tocopherols sunflower oil and flavonoids of various plants were quantified. Flavonoids derived from plant materials exhibit approximately the same amount of synergies with tocopherols (except flavonoids mint). The effect of antioxidant previously unexplored blueberry shoots was also found.
Establishment of the nature of the joint antioxidant influence of tocopherols and flavonoids to process of vegetable oils oxidation
Keywords: синергізм; безводні ліпідні субстрати; антиоксидантна активність; інгібітори; oxidation; tocopherols; flavonoids; synergy